Uticaj Embryoglue® medijuma na implantaciju humanih embriona - Pavlović Vasić, Dragana; Sibinčić, Sanja; Milaković, Irena; Lukač, Sanja; Vujnić, Saša; Gvero, Milica; Madžar, Danijela; Govedarović, Aleksandra; Ivanović, Dragan (Scripta Medica, 2021)
Introduction: Thanks to ever-growing advances in medical science, couples who are in the in vitro fertilisation (IVF) now have more options than ever to encase their chances at a successful pregnancy. One of the options is the use of EmbryoGlue (EG), that creates a bridge between the embryo and the uterus and provides protection to the embryo itself during the transfer process. Aim of this study was to determine whether EG medium is of greater importance for embryo implantation than conventional medium in assisted reproductive technology and compare the rate of embryo implantation with EG and conventional medium in relation to the quality of the embryo, the age of the patients and tobacco smoking. Methods: The retrospective study included 50 patients who used EG medium in embryo transfer (ET) and 50 patients in the control group using conventional medium. All patients underwent ET after stimulation of the cycle according to a short protocol. ETs were done on Day 2, 3, or 5 in the blastocyst stage. Age and smoking status were recorded. Results: Out of a total of 100 patients, 42 patients had successful implantation and positive β-hCG 15 days after ET. In a control group 38 % had positive β-hCG and in the group of patients who used EG 46 %. A higher rate of embryo implantation success was observed on the second day of transfer in the group of patients using EG. In the EG group a significant increase in the embryo implantation rate was observed in patients older than 35. In tobacco smokers the implantation rate was higher if they used EG during ET. Conclusion: EG medium had a positive effect on the second day of ET, patients above the age of 35 and patients who were tobacco smokers.